The role of residential habitat type on the temporal variation of wintering bird assemblages in northern Finland - Jokimäki, Jukka; Kaisanlahti-Jokimäki, Marja-Liisa (BirdLife Finland, 2012)
Wintertime ecological studies conducted in different kinds of residential areas over sev-eral winters have thus far been lacking. The objective of this study was to analyze if the between-winter variability of bird communities differs between urban residential habitat types. The study was conducted in five blocks of flats areas, five single-family house ar-eas, and five villages in Rovaniemi, northern Finland, during five winters. Birds were sur-veyed using a single-visit study plot (30 ha) method. The average between-winter varia-tion (CV%) in bird species richness was 27% and in bird abundance was 53%, and these values did not differ between the three types of residential areas. Temporal variation of species in residential areas was species-specific. The lowest between-winter variation was observed for omnivore or feeding table species such as the Great tit Parus major (50%), Magpie Pica pica (53%) and House Sparrow Passer domesticus (76%). The high-est variation was observed for berry-eating species, such as the Bullfinch Pyrrhula pyrrhula (196%) and Waxwing Bombycilla garrulus (192%). The between-winter vari-ation (CV%) of abundance of most species was greater in the blocks of flats areas than in the other residential-area types. The between-winter average qualitative similarity was 76.1% in the blocks of flats areas, 80.0% in the single-family house areas, and 78.0% in the villages, and these values did not differ between types of residential areas or between study winters. Stability of winter communities decreased from the centre to the periphery of Rovaniemi. We suggest that the stabilizing, warmer microclimate near the urban core of the town partly explains this result. The average species turnover rate (%) in the block of flats areas was 22.8, in single-family house areas was 20.5, and in the villages was 21.6. In general, the lowest between-winter similarities, highest species turnover rates, and the highest between-winter variation of abundance of individual species were observed in ar-eas of blocks ...